2020
DOI: 10.1159/000510654
|View full text |Cite
|
Sign up to set email alerts
|

The Sense of Stigmatization in Patients with Plaque Psoriasis

Abstract: Background: Psoriasis is a systemic inflammatory disease capable of creating stigmatization in the form of social exclusion and decrement of psychological conditions. Aim: The aim of the study was to determine the level of stigmatization in patients with plaque psoriasis. Methods: The study included 166 patients with plaque psoriasis (55.6% women and 44.3% men) with Psoriasis Area and Severity Index scores ≤10. The age of the study patients ranged between 18 and 72 years (arithmetic mean = 37.4; median = 38; s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 27 publications
2
16
0
4
Order By: Relevance
“…It was proved that several factors could predict the stigmatization level of patients with psoriasis, including sociodemographic variables, disease-related variables, and personality variables. Among the sociodemographic variables, gender correlated with stigmatization level in some studies (27,49), while in others not (26,34). Lower education (50), lack of professional knowledge (51), and countryside residence (52) were associated with higher levels of stigmatization, which might be secondary to inadequate understanding of psoriasis.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It was proved that several factors could predict the stigmatization level of patients with psoriasis, including sociodemographic variables, disease-related variables, and personality variables. Among the sociodemographic variables, gender correlated with stigmatization level in some studies (27,49), while in others not (26,34). Lower education (50), lack of professional knowledge (51), and countryside residence (52) were associated with higher levels of stigmatization, which might be secondary to inadequate understanding of psoriasis.…”
Section: Discussionmentioning
confidence: 94%
“…Several body regions were identified as ‘sensitive’, where psoriasis was associated with negative mental health. Another study included 166 patients with plaque psoriasis to determine their level of stigmatization and the association between the level of stigmatization and other factors ( 36 ). Men, countryside dwellers, unmarried persons, patients with a longer history of the disease had significantly higher stigmatization levels than women.…”
Section: -Item Stigmatization Scalementioning
confidence: 99%
“…A recent study showed that 51.1% of patients with psoriasis feel that society does not show tolerance for their condition, 57% of patients have received uncomfortable questions regarding their condition and 59.1% report that they have experienced discrimination because of psoriasis [ 8 ]. In another paper, approximatively 66% of patients report that they are perceived as contagious and unattractive by society at large.…”
Section: Discussionmentioning
confidence: 99%
“…Stigmatization can exacerbate negative emotions and unfavorable self-perceptions such as low self-esteem and a negative body image [ 4 , 5 ]. Stigmatization not only leads to the social exclusion of patients with psoriasis but also affects their mental status, possibly causing anxiety, anger, depression or its most serious complication, suicide [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Skin is an essential medium to both express and perceive emotions, and as such, plays a pivotal role during interpersonal contacts. The appearance of the skin and its appendages not only reflects the general body condition, but also exerts an effect on one’s self-esteem and self-image, and the way he/she is perceived by the others [ 2 4 ]. Hence, individuals suffering from various dermatological conditions have usually distorted self-image and tend to estimate their QOL as low [ 5 – 8 ].…”
Section: Introductionmentioning
confidence: 99%